Hypnosis Training and Education: Experiences with a Norwegian One-Year Education Course in Clinical Hypnosis for Children and Adolescents. Issue 3 (20th January 2017) - Lindheim, Maren Ø.; Helgeland, Helene
Abstract : Although the efficacy of clinical hypnosis is well documented, its implementation in clinical practice is far from completed and there are few reports of systematic, professional training. This article gives a historical overview and description of a 1-year training program in clinical hypnosis which started in Norway in 2008 and has been held yearly since then. We describe the present education course with respect to aims, conceptual framework, structure, target groups, teaching themes, and experiences. The following factors have been considered of importance for the success of this program: The extent and duration of the course, the focus on demonstrations, experiential skill-building and exercises, and that the education is rooted in acknowledged clinical, academic, and educational environments. The participants' evaluations tell stories of mastery and positive experiences with hypnosis as a therapeutic tool in their clinical practice. However, many struggle to understand the various concepts of hypnosis, trance, and suggestions. Some find it hard to get started and challenging to integrate hypnosis in their clinical practice. Finally, some report scarce opportunities to apply their newly acquired skills at their work places and limited support by their leaders. The development of systematic, professional training programs as described in this article may be of importance for further implementation. However, this will also require that clinicians and leaders in universities and professional environments, and policymakers at higher levels, recognize clinical hypnosis as a valid and efficient choice of treatment. This must be reflected in dedicated efforts to ensure successful implementation in practice.